Comparison of L452R mutation variant diagnosis in SARS-COV-2 PCR positive samples with two different qPCR kits - Gürer Giray, Burcu; Güven Açık, Gökçe (The European Research Journal, 2023)
Objectives: Quantitative reverse transcription‐polymerase chain reaction (qPCR) is used as the gold standard method to diagnose COVID-19 infection caused by SARS-CoV-2 which is the cause of the most important epidemic in world history. It was aimed to compare the results of two of the most commonly used commercial kits for the diagnosis of SARS-CoV-2 mutation in our laboratory during the pandemic. Methods: Our study included 5000 SARS-CoV-2 PCR positive nasopharyngeal swab samples (2500 L452R mutation positive samples, 2500 L452R mutation negative samples). PCR positivity and negativity of the L452R mutation of the positive SARS-CoV-2 positive samples were identified with the Diagnovital® (DIAGNO5plex NS SARS-CoV-2 Real Time PCR Kit [A1 Life Sciences Istanbul]) kit. The mentioned samples were also studied with a different commercial PCR kit, Bio-Speedy® (SARS-CoV-2 Emerging Plus Real Time PCR Kit [Bioeksen R&D Technologies Istanbul]). Results: A total of 5000 samples included in the study were concluded as SARS-CoV-2 positive with both tests. One hundred and fifty of 2500 samples that were found positive for SARS-CoV-2 but negative for L452R mutations with the Diagnovital® kit were found positive with the Bio-Speedy® kit for SARS-CoV-2. The compatability between the two kits was found to be high (Kappa= 0.940). The mean Ct values of the samples found positive with the Diagnovital® kit and Bio-Speedy® kit were 24.15 ± 6.75 and 20.72 ± 7.17, respectively and the difference was statistically significant. Conclusions: It was determined the two commercial kits included in the study were extremely compatible based on their analysis. Therefore both kits can be used safely for COVID-19 symptomatic patients.